Comparison of semiquantification experimental methodologies using micro‐Raman spectroscopy: palme software as an alternative tool for the study of salt efflorescence. (4th November 2016) - Costantini, Ilaria; Veneranda, Marco; Prieto‐Taboada, Nagore; Bellot‐Gurlet, Ludovic; Castro, Kepa; Madariaga, Juan Manuel
Abstract : The presence of salt efflorescence is one of the main causes of deterioration of building materials. Raman spectroscopy can be used not only to identify the different compounds present in such salts but also for the semiquantification of such salt deposits based on the use of external calibration curves. Normally, this method takes time for the preparation of pellets composed of both mixtures of standard and real samples. In the present work, we propose an innovative approach for semiquantification of salts in the solid state by portable micro‐Raman spectroscopy. It is based on the use of thepalme software (From Molecules to Nano‐objects: Reactivity Interactions and Spectroscopy–University Pierre and Marie Curie, Paris) that has been developed in order to obtain the quantitative information from the vibrational spectrum by using a multivariate linear regression approach. It considers the mixture spectra as a linear combination of the suspected pure material spectra. The aim of this work is to applypalme software to the study of pellets of standard samples composed of mixtures of calcium carbonate, gypsum and potassium nitrate at different concentrations in order to verify the reliability of this method by comparing the results with those obtained through the construction of calibration curves. Moreover, both methodologies have been tested on real efflorescence salts sampled in the San Esteban Church (Ribera de Valderejo, Basque Country, Spain). This research shows that the method based on the treatment of Raman spectra withpalme software allows to obtain in situ semiquantitative results in a much shorter time (minutes in fact), being comparable in quality with those obtained with the external calibration curve method. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : In this work, the softwarepalme was tested as an alternative to the external calibration curve procedures for the study of mixture of spectra recorded on salt samples in the solid state by using portable micro‐Raman spectroscopy. The results obtained by both quantification approaches were comparable in statistical terms, revealing that the results obtained by the external calibration and thepalme software methods are reliable. This new approach can be considered an appropriate tool for the semiquantification of salt efflorescences and for the diagnosis of porous material employed as building materials.